Comparison between Kawasaki disease with lymph-node-first presentation and Kawasaki disease without cervical lymphadenopathy - Jung Ok Kim; Yeo Hyang Kim; Myung Chul Hyun (Korean Pediatric Society, 2016)
PurposeWe evaluated the characteristics of patients with Kawasaki disease (KD) who presented with only fever and cervical lymphadenopathy on admission, and compared them with the characteristics of those who presented with typical features but no cervical lymphadenopathy.MethodsWe enrolled 98 patients diagnosed with KD. Thirteen patients had only fever and cervical lymphadenopathy on the day of admission (group 1), 31 had typical features with cervical lymphadenopathy (group 2), and 54 had typical features without cervical lymphadenopathy (group 3).ResultsThe mean age (4.3±2.1 years) and duration of fever (7.5±3.6 days) before the first intravenous immunoglobulin (IVIG) administration were highest in group 1 (P=0.001). Moreover, this group showed higher white blood cell and neutrophil counts, and lower lymphocyte counts after the first IVIG administration as compared to the other groups (P=0.001, P=0.001, and P=0.003, respectively). Group 1 also had a longer duration of hospitalization and higher frequency of second-line treatment as compared to groups 2 and 3 (group 1 vs. group 2, P=0.000 and P=0.024; group 1 vs. group 3, P=0.000 and P=0.007). A coronary artery z score of >2.5 was frequently observed in group 1 than in group 3 (P=0.008).ConclusionKD should be suspected in children who are unresponsive to antibiotics and have prolonged fever and cervical lymphadenopathy, which indicates that KD is associated with the likelihood of requiring second-line treatment and risk of developing coronary artery dilatation.